Welcome to media rhetoric: where human persuasion and technological means collide - Mateus, Samuel (2021)
The social world is made of rhetorical practices that constitute our sense of self. We are always using some kind of rhetoric exhorting others to understand our thoughts and influencing them to adopt new forms of doing and thinking. Central to persuasive communication today are Media. They not only help shape rhetoric, they are also a key means of disseminating rhetorical discourses. Media Rhetoric expression marks a fundamental stage of human communication and the development of civilization where Media became key rhetorical actors and social players. In this essay the scope of Media Rhetoric is briefly presented along with a discussion of two central fields of Media Rhetoric today - advertising and digital rhetoric. By focusing on two case-studies – a print advertising campaign by Canadian Journalists for Free Expression (CJFE) and the QuitNow app – I demonstrate how persuasive strategies evolved in mediatized societies. Closing the article, some notes on Media Rhetoric from a Policymaking perspective are offered and reasons advanced to consider it, in the near future, as an important object of public attention.